2019
DOI: 10.1093/humrep/dez099
|View full text |Cite
|
Sign up to set email alerts
|

Treatment-independent live birth after in-vitro fertilisation: a retrospective cohort study of 2,133 women

Abstract: STUDY QUESTION What is the chance of a treatment-independent live birth following IVF (including ICSI) treatment? SUMMARY ANSWER Over 5 years of follow-up, the treatment-independent live birth rate was 17% in unsuccessfully treated women and 15% in those who had a live birth after IVF. WHAT IS KNOWN ALREADY A limited number of studies have investigated the ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 29 publications
(61 reference statements)
1
11
1
Order By: Relevance
“…In the last decade, there was an increasing interest to evaluate the metabolic profile of FF in females affected by infertility in order to establish whether potential differences in the concentrations of specific compounds might be causative of, or related to infertility [21,22]. The final goal is to increase the efficiency of IVF since several clinical conditions leading to infertility (EM, PCOS, AR-ROR, ROR) are characterized by a low rate of success when these patients undergo IVF practice [23,24]. Furthermore, information on the biochemical composition of FF might be helpful not only for the comprehension of the molecular mechanisms of female infertility but also in setting up personalized therapies/diets aimed to modify the anomalous concentrations of metabolites in FF of IF [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…In the last decade, there was an increasing interest to evaluate the metabolic profile of FF in females affected by infertility in order to establish whether potential differences in the concentrations of specific compounds might be causative of, or related to infertility [21,22]. The final goal is to increase the efficiency of IVF since several clinical conditions leading to infertility (EM, PCOS, AR-ROR, ROR) are characterized by a low rate of success when these patients undergo IVF practice [23,24]. Furthermore, information on the biochemical composition of FF might be helpful not only for the comprehension of the molecular mechanisms of female infertility but also in setting up personalized therapies/diets aimed to modify the anomalous concentrations of metabolites in FF of IF [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…Age and duration of infertility are known to be significant predictors for potential spontaneous conception; younger women with a shorter duration of infertility are more likely to conceive without ART (38). Meanwhile, studies have also shown that age and duration of infertility are important factors affecting the rate of assisted reproduction in women with TFI (39). However, when it comes to endometrial thickness, which may reflect endometrial receptivity (40).…”
Section: Discussionmentioning
confidence: 99%
“…The cumulative pregnancy rate observed across up to 12 insemination cycles was 74% for women younger than 31 years, decreased to 62% for women aged 31-35 years and decreased further to 54% for women older than 35 years [2]. Therefore, the pregnancy success rate of older women is significantly reduced in regard to both natural conception and assisted reproductive technology [15,16]. Several indicators can be used to assess ovarian reserve function, including FSH, inhibin B, AMH and AFC.…”
Section: Discussionmentioning
confidence: 99%